ANALISIS PROFIT DAN EFISIENSI USAHA ITIK PETELUR SEMI-INTENSIF: PENDEKATAN BERBASIS SURVEI DI KECAMATAN SINDANG KABUPATEN INDRAMAYU - Herlina, Linda; A., Fitriani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
A business can be considered successful when it contributes to the income and meets the daily needs of the farmers. This research aims to analyze the average revenue, profit, and business efficiency of semi-intensive duck farming in Sindang Sub-district, Indramayu Regency. The research was conducted for one month in June 2021. The survey method was employed, involving 55 respondents. Both primary and secondary data were utilized, with primary data obtained through interviews using questionnaires from the main source, which is the duck farmers as respondents. Secondary data were obtained from relevant literature studies. The research findings indicate that with an average ownership of 469 laying ducks, the revenue obtained is 181,328,667 per year, with a profit of 27,418,084 per year, and a business efficiency of 1.18. Keywords: ducks layer, revenue, profit, efficiency